Relationship between Body Mass Index and Visceral Fat of Participants EXPO 2021 Universitas Teuku Umar - Adelina Irmayani Lubis; Suci Eka Putri; Safrida Safrida; Hanif Muchdatul Ayunda; Arif Iskandar (Universitas Teuku Umar, 2021)
Visceral fat levels contribute to obesity. Visceral fat is fat accumulation in fatty tissue around intra-abdominal organs or commonly referred to as central obesity. The higher the Body Mass Index, the percentage of fat mass and visceral fat will increase. Obesity can have an impact on insulin resistance, metabolic syndrome disorders and degenerative diseases. This study aims to determine the relationship between body mass index (BMI) and visceral fat. This study uses a cross-sectional design and descriptive-analytic, looking for the relationship between body mass index and visceral fat level. The result shows about 53,6% and 25% of overweight respondents with high and very high visceral fat levels. There is a relationship between body mass index and visceral fat level with p-value obtained is 0,00 (p-value < 0,05). It means that there is a risk of obesity and metabolic syndrome disorders. Prevention efforts are needed by increasing physical activity, consumption of vegetables and fruit, and routine general checks up.